The Probability of Migrant Workers Becoming Participants of BPJS for Employment - Sucihatiningsih Dian Wisika Prajanti; Wara Dyah Pita Rengga; Cepi Kurniawan (Journal of Economic Education, 2023)
Protecting migrant workers' right to social security is essential, not only to ensure equality of treatment in social security for migrant workers but also to extend social security coverage to currently unprotected populations. Migrant workers have become one of the pillars of national economic growth and contributed significantly to state revenues and economic productivity, through high remittances. Therefore, the organizers of employment social security need to increase the probability of migrant workers becoming BPJS Employment participants. By using the logistic regression method and Sakernas data for August 2021, it was found that migrant workers with work contracts and BPJS for health membership have a higher tendency to become participants in employment social security. Recommendations for membership extension for migrant workers can be made with several alternatives such as, (1) justifying or adjusting payment schemes for migrant workers who work in the informal sector abroad (2) encouraging the expansion of the coverage of migrant workers, BPJS for Employment can carry out socialization of the program by collaborating with BP2TKI and Indonesian Migrant Worker Placement Agency (P3MI) (3) It is necessary to encourage employers to register their workers in employment social security, through document requirements for the distribution of migrant workers.